Hukum Pajak Menghendaki Pemungutan Pajak Yang Adil dan Mempunyai Kepastian Hukum - Suryadi, Agus S. (LAW REVIEW, 2005)
Regulation on taxation plays a crucial role in the development of a nations economy. Not only that, it also will determine the level of welfare of the society as it is formulated and drawn from the nations gross domestic income and the ration of its budget deficit. To guarantee a success in taxing its people a government should implement clear and fair laws. This would also prevent disputes resulted from tax collection. In reality in Indonesia there is many disputes on tax occurred mainly as a result of unclear regulation. The Â settlement procedure for such disputes is in itself vague meaning no legal certainty and/or fair guarantee. One of the weaknesses of the system is that the Board of Tax Dispute Settlement does not function as a real court of law which paramount in the Supreme Court. Accordingly, the procedure does not have legal-binding power. In addition to discussing the weaknesses of the settlement procedure this article also introduces a concept of just taxation system that hopefully will help the government review and reformulate its tax policy.